Evaluation of herbicides for effective weed control in irrigated castor (Ricinus communis L.): EVALUATION OF HERBICIDES FOR EFFECTIVE WEED CONTROL IN IRRIGATED CASTOR - P M VAGHASIA; V B BHALU; R H KAVANI (Journal of Oilseeds Research, 2015)
An experiment was conducted to evaluate the efficacy of weed management practices using pre-emergence (pendimethalin and trifluralin) and post-emergence herbicides (quizalofop-ethyl and fenoxaprop-ethyl) along with weed free and unweeded check in castor (cv. GCH-6) under irrigated conditions at Main Oilseeds Research Station, Junagadh Agricultural University, Junagadh for three consecutive years during kharif 2010 to 2012. The experiment was conducted in randomised block design with three replications on medium clay soils with pH 7.9. The experimental field was infested with grasses and broad leaved weeds viz., Echinochloa colonum, Eluropus villosus, Dactyloctenium aegyptium, Brachiaria sp., Cyperus rotundus, Commelina benghalensis, Digera arvensis, Indigofera glandulosa and Amaranthus viridis. The highest castor seed yield during the study period was found in weed free control (4429, 2546 and 2581 kg/ha during yearI, II and III, respectively). Similarly, pooled mean ofseed yield (3183 kg/ha) was highest in weed free control. Among the herbicidal treatments, trifluralin @ 1.0 kg a.i./ha followed by post-emergence application of quizalofop-ethyl @ 0.05 kg a.i./ha at 25 days after sowing (DAS) recorded highest seed yield (3005 kg/ha) due to lower dry weight of weeds (374 kg/ha), higher weed control efficiency (85.9%) at 75 DAS and lower weed index (5.5%). This treatment resulted in higher gross returns (` 120208/ha), net returns (` 90398/ha) and B:C ratio (3.0). However, this was at par with application of pendimethalin @ 1.0 kg a.i./ha followed by post-emergence quizalofop-ethyl @ 0.05 kg a.i./ha at 25 DAS.